Research Advances in the Roles of Circular RNAs in Pathophysiology and Early Diagnosis of Gestational Diabetes Mellitus - Zhang, Yan-ping; Ye, Sha-zhou; Li, Ying-xue; Chen, Jia-li; Zhang, Yi-sheng (Frontiers in Cell and Developmental Biology, 2022)
Gestational diabetes mellitus (GDM) refer to different degrees of glucose tolerance abnormalities that occur during pregnancy or are discovered for the first time, which can have a serious impact on the mother and the offspring. The screening of GDM mainly relies on the oral glucose tolerance test (OGTT) at 24 to 28 weeks of gestation.The early diagnosis and intervention of GDM can greatly improve adverse pregnancy outcomes. However, molecular markers for early prediction and diagnosis of GDM are currently lacking. Therefore, looking for GDM-specific early diagnosis markers has the important clinical significance for the prevention and treatment of GDM and the management of women's full life cycle. Circular RNA (circRNA) is a new type of non-coding RNA. Recent studies have found that circRNAs are involved in the occurrence and development of malignant tumors, metabolic diseases, cardiovascular and cerebrovascular diseases, etc., and could be used as the molecular marker for early diagnosis. Our previous research showed that circRNAs are differentially expressed in serum, placental tissue and cord blood of pregnant women with GDM. Present article reviews the role of circRNAs in the pathophysiology and research progress as the molecular marker for early diagnosis of GDM.